Some Heavy metals elements in milk powder samples collected from Baghdad markets - Khalid Nassif Jassim; Omar Jaffar Alsaree (College of Pharmacy / Mustansiriyah University, 2018)
powder milk is an important foodstuff and beneficial to human health. Thirty random milk powder samples of different trade marks (Rawan® limit full milk powder), (Dielac® milk powder) and ( Fresh instant milk powder) were collected from different outlets in Baghdad capital of a IRAQ, They were analyzed by Atomic Absorption Spectrophotometer  for the concentrations of following heavy metals , lead (Pb), iron (Fe), aluminium (Al),  Cadmium (Cd),  and manganese (Mn)].  This study appeared  that the concentrations of heavy metal Fe samples is above the allowed limit in ( Rawan® limit  milk powder). However the concentrations of about thirty percent of the samples of Fe in ( Dielac full cream milk powder ) is above the allowed limits.  The concentration of Pb in ( Fresh instant full cream milk powder)   is above  the permissible limit . All the examined samples found  free of  Cd. Air, water and plants considered as a main contamination of the milk powder by heavy metals. So it is necessary for warning from the toxic effects for these heavy metals for children and adults.